Cultivating Psychological Resilience of Israeli Medical Directors of COVID-19 Divisions: The Dynamic Spheres of Salutogenics - Gillie, Gabay; Naamati-Schneider, Lior; Pikkel, Dvora (Frontiers in Public Health, 2022)
Purpose: There are a few qualitative studies on the psychological resilience of COVID-19 medical directors upon outbreaks of pandemics. Psychological resilience is essential to providing quality care through the pandemic. Materials and Methods: We conducted narrative interviews with 14 out of 21 medical directors of COVID-19 divisions in Israeli public hospitals upon the outbreak of the pandemic and through its first wave. We adopted the Salutogenic paradigm to identify personal and organizational resources that both deterred and promoted the resilience of front-line medical directors. Thematic analysis was performed based on the Sense of coherence construct, an anchor of Salutogenics. Results: Low comprehensibility was compensated by ethical boundaries and managerial experience. A few organizational and personal resources promoted manageability. The hospital management both deterred and promoted resilience. In contrast to Salutogenics theory, meaningfulness was driven by the occupational calling rather than by comprehensibility and manageability. Gaps in personal resources inhibited resilience. Conclusions: Group-level interventions to promote resilience are a). Enable mechanisms for clinicians to share their coping behaviors with others. b). Establish a network of clinicians to carry on an organizational discourse of peer support with whom to share experiences in chaotic times. c). Identify, select, and use available organizational resources while adapting to adversity in order to facilitate more effective responses of clinicians [14, 54]. On a systemic level (i.e., division or hospital), management is called upon to: a). Assign a designated mental health professional to improve the buffering of stress [55,56]; b). Develop ethical awareness by structuring ongoing discussions on significant ethical concerns that may arise during a crisis. c). Support real-time ethical reflections d). Safeguard clinicians and their well-being. Our study adds to the scant qualitative research performed upon the outbreak of the pandemic and extends the Salutogenic paradigm suggesting that the three axes of sense of coherence are multi-layered, intertwined, and evolving. We introduce the dynamic spheres model that we adopted from Physics to illustrate the findings. We propose interventions to build resilience in front-line medical directors.